Vulvar Fibroadenoma with regards - Susana Hernández Delgado; Javier Martínez Navarro (Centro Provincial de Información de Ciencias Médicas. Cienfuegos, 2018)
Vulvar fibroadenoma is extremely rare. It presents as a unilateral mass of variable size, asymptomatic and occasionally associated to other vulvar and extra-vulvar lesions. There is a great controversy about their origin. These lesions need a histo-pathological exam to reach a concluding diagnosis. Its behavior is similar to the breast tumor. Its removal generally has a good prognosis and there is rarely a relapse. This is a case of a 26 year old woman who was histo-pathologically diagnosed a vulvar tumor. A surgical removal was performed.